2020
DOI: 10.1186/s12891-020-03664-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between anterior bone loss and anterior heterotopic ossification in hybrid surgery

Abstract: Background Hybrid surgery (HS) has become an alternative procedure for the treatment of multilevel cervical degenerative disc disease with satisfactory outcomes. However, some adverse outcomes have recently emerged, such as heterotopic ossification (HO) and anterior bone loss (ABL). Furthermore, HO was found mostly located in the posterior and lateral of the cervical intervertebral disc space. The mechanism of anterior heterotopic ossification (AHO) formation may be different, and its relationship with ABL was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…Main Complication after CDA HO and ABL were the main complications after CDA, 14,42 and were currently considered two stages of bone remodeling following CDA surgery. 43 In the present study, the incidence of HO, high-grade HO, and ABL at the arthroplasty levels did not differ significantly between the CDA and HS groups at the last follow-up. Moreover, the incidence of HO and ABL was consistent with previous studies on 1-level or contiguous 2-level CDA.…”
Section: Cda Presents Biomechanical Advantagescontrasting
confidence: 46%
“…Main Complication after CDA HO and ABL were the main complications after CDA, 14,42 and were currently considered two stages of bone remodeling following CDA surgery. 43 In the present study, the incidence of HO, high-grade HO, and ABL at the arthroplasty levels did not differ significantly between the CDA and HS groups at the last follow-up. Moreover, the incidence of HO and ABL was consistent with previous studies on 1-level or contiguous 2-level CDA.…”
Section: Cda Presents Biomechanical Advantagescontrasting
confidence: 46%
“…Besides, the ASD and subsidence rates were comparable among the groups. The results showed that the postoperative clinical outcomes largely depend on adequate decompression in ACDF [ 21 , 35 ]. Given this, restoring and maintaining cervical lordosis curvature is another goal that we pursue in ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…Heterotopic ossification (HO) was using the McAfee classification [ 19 ] (Table 1 ). The classification of bone loss (BL) followed a validated methodology detailed in full elsewhere, based on a classification system reported by Saleh et al in 2004 [ 20 , 21 ] (Table 2 ). For patients with two-level CDR, the more severe degree of HO and BL was recorded.…”
Section: Methodsmentioning
confidence: 99%